ADVANCEMENT AND SETBACK IN ISLAMIC BANKING PRODUCTIVITY IN ASEAN: DO TECHNOLOGICAL CHANGES MATTER? - Aam Slamet Rusydiana; Aisyah Assalafiyah (Bank Indonesia, 2021)
This study applies Data Envelopment Analysis (DEA) to measure the efficiency level of 24 Islamic banks in four ASEAN countries (Indonesia, Malaysia, Brunei Darussalam and Thailand) over the 2010-2019 period. Specifically, this study uses the Banker, Charnes and Cooper (BCC) model as a basic approach in DEA with variable return to scale assumption. The Malmquist index was also employed to explain whether the changes in Islamic banks’ efficiency and productivity is affected by the efficiency changes or technological changes. According to the Malmquist index scores on total factor productivity (TFP) change, 17 of the 24 Islamic banks (or 70.8 percent) achieved an improvement in productivity over the research period, with Thailand recording the highest productivity level increase. Overall, the most productive Islamic bank was Affin Islamic Bank Berhad. Finally, it was observed that there was a productivity growth in the last two years of the period, namely 2017-2018 and 2018-2019. The productivity change was driven more by efficiency than by technology, implying that Islamic banks in ASEAN countries must improve the technological aspect.